Knee extension rate of torque development and peak torque: associations with lower extremity function. Issue 3 (23rd March 2018) - Osawa, Yusuke; Studenski, Stephanie A.; Ferrucci, Luigi
Abstract: Background: With aging, the ability to generate muscle force decreases, contributing to declines in physical functions such as walking. While most studies assess muscle force by peak torque, the rate of torque development (RTD) reflects a dynamic component of muscle performance that is important for physical function. Using data from the Baltimore Longitudinal Study of Aging, we assessed whether RTD adds significantly to peak torque in associations with lower extremity performance. If so, RTD may help identify weak older adults for screening and intervention. Methods: We assessed associations of RTD and peak torque with physical performance independent of demographics, BMI, body composition, and each other in 1089 Baltimore Longitudinal Study of Aging participants (49.7% women; aged 26 to 96 years; women, 64.0 ± 13.8 years; men, 68.4 ± 14.4 years). Peak torque was assessed by isometric and 30 deg/s isokinetic knee extension tests. Peak RTD was operationalized as the maximum torque‐time slope among successive 50 ms epochs over the first 3 s of a test of knee extension isometric strength, with the knee joint positioned at 120 deg of flexion. A battery of lower extremity performance tests included gait speed during a 6 m walk at usual and fast pace (6 m usual and fast), time to complete a 400 m walk at fast pace (400 m), distance covered in a 2.5 min walk at normal pace (2.5 min), time to complete 5 and 10 chair stands, and two summary tests of lower extremity performance. Sex‐stratified generalized linear regression models were adjusted for age, race, BMI, appendicular lean mass, and whole body fat mass. Results: In men, independent of either measure of peak torque and cofactors, RTD was a significant ( P < 0.05) predictor of all lower extremity performance tests except the 400 m and 2.5 min walks. In women, independent of peak torque, RTD was only a significant independent correlate of the 6 m fast walk ( P < 0.001). Conclusions: RTD independently contributes to physical functions in men but less in women. The mechanisms underlying the sex difference are unclear and require further study.